Pengaruh Insentif dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan pada PT. Infomedia Nusantara - Abdi Sugiarto; Iqbal Ramadhan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
The purpose of this research is to find out what are the incentives and work discipline on the work productivity of employees at PT Infomedia Nusantara. This type of research is associative with the entire population of Infomedia call center services that open 156 employees, and the number of samples uses a Slovin sample which opens 88 employees. The form of the instrument used was a questionnaire with a Likert scale, the incentive questionnaire consisted of 7 statements, 9 questionnaire work disciplines and the questionnaire product consisted of 7 statements, all of the questionnaires were tested for validity and reliability. From the results of the questionnaire distribution for the incentive variable (X1), 58.4% agree, and 38.6% strongly agree, for the work discipline variable (X2), 60.2% agree, and 28.4 strongly agree, and for the productivity variable. obtained 68.8% agree and 28.6% strongly agree. From these data, it has fulfilled the classical assumption tests such as normality test, heteroscedasticity test, and multicollinearity test, and continued with hypothesis testing, t-test to determine partial effect and F-test to determine simultaneous effect. The conclusion obtained from the hypothesis test is that there is a partial or simultaneous influence of incentives and work discipline on the productivity of PT. Infomedia Nusantara. The influence of incentives and work discipline on productivity is 56.8%.